Music, Church, and Ethnocentrism - Smalley, William A. (Practical anthropology, 1962)
It was more by accident than by design that the articles which comprise this special issue on “Developing Hymnology in New Churches” have been brought together. They all came to my attention about the same time, and they have been published together because they rather complement each other.